Hubungan antara Kecemasan Finansial dengan Kesejahteraan Psikologis pada Mahasiswa Rantau Tingkat Akhir Universitas X - Brainy Fadli Adi Putra; Damajanti Kusuma Dewi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Background: Final-year non-local students face compounded structural vulnerability, navigating peak academic demands while independently managing their finances without direct family support. Objective: This study examined the relationship between financial anxiety and psychological well-being among final-year non-local students at Universitas X. Methods: A quantitative correlational design was employed with 250 participants selected through purposive sampling. Financial anxiety was measured using an adapted scale based on Archuleta et al. (2013) (16 items, 5 subscales, α = 0.937) and psychological well-being was assessed using an adapted PWB-18 scale based on Ryff's six dimensions (18 items, α = 0.890). Spearman's rank correlation was applied as data were not normally distributed. Results: A significant negative relationship was found between financial anxiety and psychological well-being (r = −0.469; p < 0.001; r² = 0.220), indicating that perceived financial pressure is associated with diminished psychological functioning. Conclusion: These findings provide an empirical basis for developing student support programs that address the psychological dimensions of financial pressure among non-local students, not merely its economic aspects.